A Study on the Lubrication and Cooling Mechanism of Nano–Silicon Carbide Cutting Fluids for Diamond-Wire Sawing. Issue 5 (25th August 2022) - Wang, Hongbing; Yao, Chunyan; Chen, Dongdong; Xu, Kaixiang; Sheng, Tianwei
Abstract: In the process of cutting polysilicon with a diamond-wire saw, cracks parallel to the scratch direction on the wafer surface will affect edge breakage and the fracture strength of wafers. The generated heat during the process of cutting can cause warpage of wafers. In order to reduce the generation of cracks and the heat, and to improve cutting performance, new cutting fluids with nano–silicon carbide (N-SiC) named nano-silicon cutting fluids (NSCF), which improve the lubrication and cooling performance of cutting fluids, were researched, and their lubrication and cooling mechanism in diamond-wire sawing was studied. The polysilicon cutting experiment was carried out by using NSCF. Research results show that the lubrication film caused by chemical reaction and physical adsorption was formed on the wafer surface under the lubrication of NSCF, which can greatly reduce the cracks-generation on the wafer surface. The N-SiC particles can effectively enhance the heat-transfer performance of cutting fluids and effectively cool the cutting area. So, the NSCF can effectively improve the cutting performance of diamond-wire sawing. The width of kerfs and edge breakage reach the lowest value when the mass fraction of N-SiC is 0.3 wt%. The surface roughness reaches the lowest when the mass fraction of N-SiC is 0.2 wt%.